Characterization of Al-Doped ZnO Transparent Conducting Thin Film Prepared by Off-Axis Magnetron Sputtering. (8th August 2016) - Ou, Sin-Liang; Lai, Feng-Min; Yuan, Lun-Wei; Cheng, Da-Long; Kao, Kuo-Sheng
Abstract : The off-axis sputtering technique was used to deposit Al-doped ZnO (AZO) films on glass substrates at room temperature. For the illustration of the sample position in the sputtering chamber, the value ofR / r is introduced. Here, r is the radius of AZO target and R is the distance between the sample and the center of substrate holder. A systematic study for the effect of deposition parameters on structural, optical, and electrical properties of AZO films has been investigated in detail. As the sample position ofR / r is fixed at 1.8, it is found that the as-deposited AZO film has relatively low resistivity of 2.67 × 10 −3  Ω-cm and high transmittance above 80% in the visible region. Additionally, after rapid thermal annealing (RTA) at 600°C with N2 atmosphere, the resistivity of this AZO film can be further reduced to 1.19 × 10 −3  Ω-cm. This indicates the AZO films prepared by off-axis magnetron sputtering and treated via the appropriate RTA process have great potential in optoelectronic applications.